REGIONAL HUMAN CAPITAL: PROBLEMS OF ESSENCE, STRUCTURE AND ASSESSMENT - Olga V. Zabelina; Tatiana M. Kozlova; Alexander V. Romanyuk (Статистика и экономика, 2016)
This article considers main questions appear in comtemporary circumstances while studying human capital on regional level: problems of understanding and aggregation, human capital structuring and assessment.